Desain dan Implementasi Website di Pondok Pesantren Darul Fithrah - Fitriani, Sofy; Sofyan, Yusuf; Soewono, Eddy Bambang; Setiarini, Siti Dwi; Noviansyah, Beri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Darul Fithrah Islamic Boarding School is an Islamic educational institution that aims to provide its students with religious education, formal education, and character development. A community service theme related to the school website is proposed to increase communication efficiency, information transparency, and interaction between Islamic boarding schools, students, parents, and the community. This website design uses structured stages. The first stage is planning, training, evaluating, and making activity reports. At the planning stage, the features that will be displayed on the website are adjusted to the Islamic boarding school's needs. After the website is completed, information system training is carried out on the website. The evaluation stage is carried out to monitor if problems occur. Based on the results of monitoring and evaluation, the website created makes it easy for various parties to obtain and share information related to Islamic boarding schools, and the website has been well optimized so that it has entered the first page on the Google search engine in fourth place.